2010
DOI: 10.1089/jop.2009.0076
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Ocular Hypertension Following Intravitreal Bevacizumab and Ranibizumab Injections

Abstract: Persistent OHT may occur after intravitreal anti-VEGF injection in patients with no previous diagnosis of glaucoma or OHT. OHT may persist across several visits and patients may require IOP-lowering therapy. Sustained elevation in IOP usually occurs after multiple injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 18 publications
6
126
3
2
Order By: Relevance
“…No instances of endophthalmitis were reported in this study. In addition, the instances of vitreous hemorrhage, hypersensitivity reaction, traumatic cataract, retinal tear, and retinal detachment were infrequent per injection (0 to 0.1% of injections) and per patient (0 to 0.8% of patients).In this study, increased IOP was the most frequently reported POAE (6.6% per patient), which is consistent with the reported incidence of increased IOP in a mixed disease population (ranges from 3.4% to 11% per patient) [15,16]. Abbreviations: AMD = age-related macular degeneration, N = number of patients in each treatment group, n = number of patients with a response, POAE = pertinent ocular adverse event, IOP = intraocular pressure, CI = confidence interval, SD = standard deviation *Incidence rate per patient: the number of patients with specific POAEs divided by the total number of patients that received injections in treated eye(s)…”
Section: Discussionsupporting
confidence: 89%
“…No instances of endophthalmitis were reported in this study. In addition, the instances of vitreous hemorrhage, hypersensitivity reaction, traumatic cataract, retinal tear, and retinal detachment were infrequent per injection (0 to 0.1% of injections) and per patient (0 to 0.8% of patients).In this study, increased IOP was the most frequently reported POAE (6.6% per patient), which is consistent with the reported incidence of increased IOP in a mixed disease population (ranges from 3.4% to 11% per patient) [15,16]. Abbreviations: AMD = age-related macular degeneration, N = number of patients in each treatment group, n = number of patients with a response, POAE = pertinent ocular adverse event, IOP = intraocular pressure, CI = confidence interval, SD = standard deviation *Incidence rate per patient: the number of patients with specific POAEs divided by the total number of patients that received injections in treated eye(s)…”
Section: Discussionsupporting
confidence: 89%
“…74,75 While some patients respond to intravitreal injection with sustained elevation of IOP, most do not even after multiple injections. [76][77][78][79][80][81][82] In our study, we performed intravitreal injection of drug-loaded NS once and observed IOPlowering effects out to 32 days (Fig. 4).…”
Section: Discussionmentioning
confidence: 62%
“…Although intravitreal injections and sustained release devices deliver adequate drug levels to the retina, repeated intraocular injections as well as surgical placement of intravitreal implants are associated with complications such as cataracts, elevated intraocular pressure, hemorrhage, retinal detachment, and endophthalmitis (Adelman et al, 2010;Sampat and Garg, 2010;Sato et al, 2010). To overcome the risks associated with intravitreal route and to improve on inefficient drug delivery to the back of the eye after topical and oral administration, periocular/transscleral routes such as subconjunctival and subtenon routes may offer more promising alternatives for retinal drug delivery (Cruysberg et al, 2002;Ayalasomayajula and Kompella, 2004;Raghava et al, 2004).…”
Section: Introductionmentioning
confidence: 99%